Subthalamic deep brain stimulation improves sleep and excessive sweating in Parkinson’s disease - Bjerknes, Silje (NPJ Parkinsons Dis, 2020)
Parkinson’s disease (PD) is a complex multisystem disorder with motor and non-motor symptoms (NMS). NMS may have an even greater impact on quality of life than motor symptoms. Subthalamic nucleus deep brain stimulation (STN-DBS) has been shown to improve motor fluctuations and quality of life, whereas the effects on different NMS have been less examined. Sleep disturbances and autonomic dysfunction are among the most prevalent NMS. We here report the efficacy of STN-DBS on sleep disturbances and autonomic dysfunction. In the parent trial, 60 patients were included in a single-center randomized prospective study, with MDS-UPDRS III and PDQ-39 as primary endpoints at 12 months of STN-DBS. Preplanned assessments at baseline and postoperatively at 3 and 12 months also included Parkinson’s Disease Sleep Scale (PDSS); Scopa-Aut; and MDS-UPDRS I, II, and IV. We found that STN-DBS had a significant and lasting positive effect on overall sleep quality, nocturnal motor symptoms and restlessness, and daytime dozing. Several aspects of autonomic dysfunction were also improved at 3 months postoperatively, although at 12 months only thermoregulation (sudomotor symptoms) remained significantly improved. We could not identify preoperative factors that predicted improvement in PDSS or Scopa-Aut. There was a close relationship between improved autonomic symptoms and improved quality of life after 1 year. NMS and especially sleep and autonomic dysfunction deserve more focus to improve patient outcomes further.